Ross and Wilson anatomy & physiology in health and illness - Waugh, Anne; Grant, Allison (Churchill Livinstone Elsevier, 2014)
Introduces the structure and functions of the human body and the effects of disease or illness on normal body function. Uses easy-to-understand language and clear color illustrations to make learning more visual and engaging.